2023
DOI: 10.57125/fed.2023.25.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Features of the organization of distance learning in the process of training specialists in administration and public administration (Polish experience)

Abstract: The article reflects the peculiarities of distance learning organization in the process of training specialists in administration and public administration on the example of the Polish experience. The methods of providing distance education, the challenges faced by specialists in higher education, and the advantages of such training of managers are considered. The presented article contains a review of the literature concerning distance learning in administration and public administration published in the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In particular, Bakhmat et al (2023) identified the peculiarities of the functioning of the modern digital educational environment, focusing on the advantages and disadvantages of digital education. Sanetra-Półgrabi (2023) addressed similar issues in the Polish experience, demonstrating the transition from traditional forms of education to the widespread use of digital technologies on the example of transformations in a post-socialist country of the former Soviet Union. The key aspects of distance learning are described in Wong et al (2021).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In particular, Bakhmat et al (2023) identified the peculiarities of the functioning of the modern digital educational environment, focusing on the advantages and disadvantages of digital education. Sanetra-Półgrabi (2023) addressed similar issues in the Polish experience, demonstrating the transition from traditional forms of education to the widespread use of digital technologies on the example of transformations in a post-socialist country of the former Soviet Union. The key aspects of distance learning are described in Wong et al (2021).…”
mentioning
confidence: 76%
“…Accordingly, a promising area of online education development is the development of digital literacy among teachers and educators. Many modern scholars emphasise this aspect (Saienko et al, 2022;Sanetra-Półgrabi, 2023;White et al, 2023). In particular, the study by Saienko et al (2022) defines digital literacy as a set of skills and knowledge necessary for the effective use of technology, especially the Internet and digital devices.…”
Section: Discussionmentioning
confidence: 99%